2020
DOI: 10.1111/hepr.13502
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive diagnosis of non‐alcoholic steatohepatitis and advanced fibrosis in Japan: A targeted literature review

Abstract: Despite the invasive nature of liver biopsy, it remains the current standard for diagnosing non‐alcoholic steatohepatitis (NASH) and fibrosis staging. Given the rising prevalence of non‐alcoholic fatty liver disease (NAFLD) in Japan, there is a need for reliable non‐invasive tests to accurately and efficiently identify NASH and advanced (F3/F4) fibrosis. A review of published works from English and Japanese sources was undertaken in PubMed, Embase, and Ichushi Web to identify studies reporting diagnostic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Liver biopsy is now the gold standard for evaluating hepatic fibrosis, but it has several drawbacks such as hemorrhage risk, invasiveness, cost, observers’ variability, and patients’ unwillingness. Considering a large population of MAFLD patients, non-invasive tests (NITs) without performing liver biopsy are urgently required [ 13 ]. The American Association for the Study of Liver Disease (AASLD) practice guidance 2018 recommends the use of an NAFLD fibrosis score (NFS), the fibrosis-4 (FIB-4) index, vibration-controlled transient elastography (VCTE), and magnetic resonance elastography (MRE) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liver biopsy is now the gold standard for evaluating hepatic fibrosis, but it has several drawbacks such as hemorrhage risk, invasiveness, cost, observers’ variability, and patients’ unwillingness. Considering a large population of MAFLD patients, non-invasive tests (NITs) without performing liver biopsy are urgently required [ 13 ]. The American Association for the Study of Liver Disease (AASLD) practice guidance 2018 recommends the use of an NAFLD fibrosis score (NFS), the fibrosis-4 (FIB-4) index, vibration-controlled transient elastography (VCTE), and magnetic resonance elastography (MRE) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…While liver biopsy is the gold standard to diagnose NASH and its severity, it is invasive and costly. There have been advances in non-invasive diagnostic methods, in particular validated predictive score models, serum markers representative of liver fibrosis, and advanced non-invasive imaging techniques [ 60 ].…”
Section: Clinical Approach To Nafld and Nafld-related Hccmentioning
confidence: 99%
“…FIB-4 is a simple formula for detecting liver fibrosis using age, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and platelet counts, and several studies have reported its high diagnostic accuracy for liver fibrosis, as well as HCC development or occurrence of complications [20][21][22][23][24][25]. Screening for fibrotic NAFLD patients with FIB-4 is currently recommended in the American Association for the Study of Liver Disease guidelines.…”
Section: Introductionmentioning
confidence: 99%